The urgency of moral aqeedah education and religious moderation for the millennial generation - Rina Rehayati; Kasmuri Kasmuri; Suhertina Suhertina; Nurhasnawati Nurhasnawati; Sariah Sariah (Jurnal Konseling dan Pendidikan, 2023)
As agents of change, millennial must be able to adapt to new situations and overcome challenges with negative effects. Moral education has helped millennial adopt moderate religious values. Therefore, this study examined aqeedah, moral, and religious moderation education of millennial. Data was collected through systematic, transparent, and reproducible literature reviews, which were used to discover, analyze and synthesize varied studies. A connected paper platform facilitated exploring different literature and identifying keyword-related literature. Descriptive analytics were used to analyze and summarize the data. The result showed that moral aqeedah education must be used to teach millennial age strong values, tolerance, and peace to achieve religious moderation. Furthermore, home, school, and community moral education must start with aqeedah to teach them religious moderation.